PENGARUH HUMAN CAPITAL DAN PERSON-ENVIRONMENT FIT TERHADAPKOMITMEN ORGANISASI - SUKARTI, (Jurnal Ilmu Manajemen (JIM), 2014)
Abstract: This research is the study of causality (Cause–Effect) which uses a quantitative approachment. This research consists of the independent variable (X). That is Human capital (X1) and Person-environment fit (X2), the dependent variable (Y), That is the commitment of the organization (Y). The objects of the research are all employees of PT Aplikanusa Lintasarta in Surabaya, with population and the samples are 50 employees who were saturated sampling.it is sample determination techniques when all members of a population is used as a sample. Statistical analysis by using Partial Least Squares (PLS) version 1.0 and SPSS version 18.The research results showed that human capital gives significant and positive influences to the organizational commitment on PT Aplikanusa Lintasarta Surabaya, person-environment fit has positive and significant influence to the organizational commitment on PT Aplikanusa Lintasarta Surabaya. Keywords :human capital, person-environment fit, and commitment organizational.